Modern Trends of Development of Industrial Tourism for Russian Universities - P, Krovopuskov; E, Kantaryuk; M, Chernyshova (International Journal of Engineering and Technology, 2018)
The paper deals with the coastal tourism in Iran and the United Arab Emirates by identifying the impact of tourist attractions on the development of coastal tourism in both countries, and the role of coastal tourism (beach, landscape, etc.) in attracting tourists in the two countries. In the present study, we investigated the environmental-ecological, socio-cultural, historical-political, economic, institutional-managerial and physical-spatial dimensions of the study area. The topicality of this work is the industrial tourism development. It will allow to enhance the economic potential of the regions, increase the flow of "domestic touristsÂ» and improve the competitiveness of enterprises in the Region. It has been studied the prospects of industrial tourism development for students of universities in Russia and directly in the Lipetsk region at the present stage of development of the machine- and lathe-building industry.Â Â
Keywords: Tourist industry; modern development; University